“En el proceso civil ecuatoriano se debe permitir la intervención de los menores de edad como parte en los procesos judiciales en los que tenga interes como alimentos, divorcio, investigación de paternidad, por lo que se debe reformar el código de procedimiento civil” - Daqui Usca, Lionso Fernando (2015)
Is constitutionally given access to justice and opportunities of people, regardless of gender, race, age, sexual identity, political ideology, religious beliefs, to obtain a satisfactory response to its legal and judicial needs. So access to justice is a material budget for the enforcement of rights and in particular to ensure the fundamental right to justice, while the access to justice should result in the removal of barriers, defined as any form of discrimination, particularly discrimination based on age, sex, gender, ethnic and racial or cultural and geared towards the promotion and protection of human rights and respect for diversity, thus contributing to the strengthening of democracy. The institutional policy of the judiciary led to effective access to justice for children and adolescents, lays down provisions that guide the staff members of the Judiciary of Ecuador to make access to justice in reality the services provided to the population under age by the Judiciary policy complies with international law that protects the rights of minors and implements regarding the right of access to justice for persons in vulnerable conditions, which minors can do without these are not represented by a guardian personally opinions or suggestions are not taken into account by judges. The jurisdiction encompassing policies as childhood and adolescence, family, domestic violence, food, labor, civil pensions, and all those cases where minors fall victim, but in the case of divorce of their parents or others in the that is relevant to their interests cannot be part of the processes that prevail in other legislation. The policy is directed and required for implementation of the involvement of all civil servant forming the judiciary, as well as those that are related to efforts or actions of minors to the judicial instance: lawyers and lawyers, organizations civil society, other institutions involved with Children, this policy and its action plan should be implemented responsibly by all civil servants and not only by those who usually attend related rights of minors cases, but this is There needs to be a norm in which guide conflicting parties and those who have to solve cases of this matter. Justice for children and adolescents should be a national system of comprehensive protection of civil society, international organizations and children and adolescent users who must give operators the judicial system, the process in which it is to through a child, a teen girl, to make access to justice in the services provided specific guidelines fact, the policy applies to all jurisdictions in those processes involving minors, It is known that the effectiveness of the exercise of a right depends, first, their knowledge so it becomes an unavoidable commitment to a dual purpose that operators and operators of the system's known and applied, as it is addressed to appropriate her to claim and demand their rights, which at the moment cannot be effective because it does not exist specifically the Code of Childhood and Adolescence Civil Code, neither provisions in which minors can be part of the processes that relate to their personal and legal rights.